The Arabidopsis Plant Intracellular Ras-group LRR (PIRL) Family and the Value of Reverse Genetic Analysis for Identifying Genes that Function in Gametophyte Development - Nancy R. Forsthoefel; Kendra A. Klag; Barbara P. Simeles; Rachel Reiter; Lauren Brougham; Daniel M. Vernon (Plants, 2013)
Arabidopsis thaliana has proven a powerful system for developmental genetics, but identification of gametophytic genes with developmental mutants can be complicated by factors such as gametophyte-lethality, functional redundancy, or poor penetrance. These issues are exemplified by the Plant Intracellular Ras-group LRR (PIRL) genes, a family of nine genes encoding a class of leucine-rich repeat proteins structurally related to animal and fungal LRR proteins involved in developmental signaling. Previous analysis of T-DNA insertion mutants showed that two of these genes, PIRL1 and PIRL9, have an essential function in pollen formation but are functionally redundant. Here, we present evidence implicating three more PIRLs in gametophyte development. Scanning electron microscopy revealed that disruption of either PIRL2 or PIRL3 results in a low frequency of pollen morphological abnormalities. In addition, molecular analysis of putative pirl6 insertion mutants indicated that knockout alleles of this gene are not represented in current Arabidopsis mutant populations, suggesting gametophyte lethality may hinder mutant recovery. Consistent with this, available microarray and RNA-seq data have documented strongest PIRL6 expression in developing pollen. Taken together, these results now implicate five PIRLs in gametophyte development. Systematic reverse genetic analysis of this novel LRR family has therefore identified gametophytically active genes that otherwise would likely be missed by forward genetic screens.